Photobleaching and stabilization of carbon nanodots produced by solvothermal synthesis. Issue 1 (30th November 2015) - Wang, Wenshuo; Damm, Cornelia; Walter, Johannes; Nacken, Thomas J.; Peukert, Wolfgang
Abstract : In this work we performed a detailed investigation of the photostability of bottom-up produced carbon nanodots (CDs) prepared from citric acid and urea by solvothermal synthesis. Abstract : In this work we performed a detailed investigation of the photostability of bottom-up produced carbon nanodots (CDs) prepared from citric acid and urea by solvothermal synthesis. Analytical ultracentrifugation (AUC) reveals that the CDs have a hydrodynamic diameter of <1 nm and a very narrow size distribution. In the community it is widely assumed that CDs are photo-stable. In contrast, we found that CDs exposed to UV-irradiation exhibit noteworthy fluorescence degeneration compared to freshly prepared CDs or CDs stored in the dark, indicating that fluorescence bleaching is caused by a photochemical process. We found that fluorescence intensity decay due to exposure to UV-irradiation is accelerated in the presence of oxygen and identified the surface status of CDs as the decisive factor of fluorescence bleaching of CDs. Based on a discussion on the underlying mechanisms we show how to avoid photobleaching of CDs.